PENGGUNAAN KURVA CT BIPLOT UNTUK ANALISIS DIALEL SIFAT BERGANDA PADA KACANG HIJAU (Vigna radiata L. Wilczek) - Edizon Jambormias; Johan Marthin Tutupary; Jacob Richard Patty (Zuriat, 2012)
Diallel analysis of multiple traits is a comprehensive approach to evaluate general combining ability (gca), specific combining ability (sca) and reciprocal effects of parents and it crosses by involving many traits simultaneously. Describing of cross-by-traits biplot (CT Biplot) can be used to describe the multiple traits diallel analysis. In order to improve the yield potential, four parents of the local varieties and two parents of the high yielding varieties of mungbean were evaluated their multiple traits combining ability by using Griffing Methods I. Results of the research show, there are 3 meaning sectors (MS) and 2 non-meaning sectors (NMS) of crosses and multiple traits. The parents Lasafu Lere Butsiw (LLBs) and Gelatik contained high gca in one MS which associated with traits of the grain weight, number of seeds per pod, number of seeds, number of filled seeds, number of pods, and number of filled pods (MS-1). The parents Lasafu Lere Butsiw fer Namamas (LLBfN), Lasafu Lere Butnem (LLBn), and variety No. 129 in the next MS (MS-3) related to the 100 seed weight trait, meanwhile the parent Mamasa Lere Butnem (MLB) located in another NMS, contained high gca for an ideal type of short plant. Crosses combination of Gelatik × LLBs, Gelatik × LLBfN, and MLB  × LLBn were vertex crosses on MS-1 and therefore, having high sca for the traits that mutually-correlated in the sector. In the other two MS sectors, the parents LLBn and LLBs were vertex genotype, so that crosses that have best sca were not found. Reciprocal effects can be viewed in some crosses, which LLBs × Gelatik was the cross combination with the highest reciprocal effects.